Analysis of Students' Conceptual Understanding When the Discovery Learning Learning Model is Applied: Does It Have a Real Impact? - Boby Syefrinando; Cici Pramita; Tasa Ratna Puri; Ayu Sofna; Al Fajri Adha; Rika Rahmadani putri; Fauzan Sulman (Edumaspul: Jurnal Pendidikan, 2023)
This research aims to determine the effect of the discovery learning model on students' understanding of concepts. This research is quasi-experimental research or quasi-experimental research. This research only uses posttests or final tests after being given treatment. The design used was Posttest Only Control Group Design. The research results showed that the average score of experimental class students who used the discovery learning model was 55.44, a maximum of 100, a minimum of 0, and a standard deviation value of 30.072. For the control class using the conventional model, the average score of experimental class students is 40.09, the maximum is 79, the minimum is 0, and the standard deviation value is 25.693. This also shows a positive impact if learning is implemented using the Discovery Learning learning model.